Antecedents of customer loyalty (CL) in the mobile telecommunication companies in Cameroon - Marymagdaline E. Tarkang; Ruth N. Yunji; Simplice Asongu; Uju V. Alola (African Governance and Development Institute (AGDI), 2021)
The mobile telecommunication (telecom) sector has become the basic source of information now-a-days especially in Cameroon. It is used to transfer and deliver information through voice, video, data, graphics, and more at perpetually increasing speeds. The quality of mobile services does not only impact the attraction of new customers but also to maintain the existing ones. The study uses relationship marketing theory and a quantitative and cross-sectional method with 200 respondents. Information was obtained from users of MTN and Orange mobile telecommunication networks. The analyses were done using SPSS version 20. Tangibility, reliability, and assurance dimensions of staff service quality showed a positive relationship with customer loyalty in mobile telecom companies in Cameroon. The findings also highlight the influence of service quality dimensions on customer loyalty in the mobile telecom companies of the country. This study complements to extant literature by examining the influence of the five service quality dimensions; tangibility, reliability, assurance, responsiveness, and empathy on consumer loyalty or retention in the mobile telecommunication companies in Cameroon.
Keywords: 330; Tangibility; Reliability; ICT; Empathy; Responsiveness; Assurance; customer loyalty